Responses of Soil Microbial Community and Enzyme Activities to Shrub Species Artemisia gmelinii in Relation to Varying Rainfall in a Semiarid Land, SW China - Qu, Laiye; Wang, Bingbing; Zhang, Xinyu; Wang, Minggang (Frontiers in Environmental Science, 2021)
Widely-distributed shrubs in drylands can locally alter soil physiochemical properties, which distinguishes soil under plant canopy from soil outside the canopy. In present study, we used a dominant shrub species Artemisia gmelinii in a semiarid land SW China, to investigate consequences of “shrub resource islands” for soil microbial communities and enzymatic activities. Such investigation was made at four sites that differed in rates of rainfall to examine how the consequences were altered by variation in local climate. The results showed that A. gmelinii enhanced fungal abundance but did not influence bacterial abundance, resulting in higher total microbial abundance and fungal:bacterial ratio in under-canopy soil compared to outside-canopy soil. Microbial community composition also differed between the two soils, but this difference only occurred at sites of low rainfall. Redundancy analysis revealed that such composition was attributed to variation in soil water content (SWC), bulk density (BD) and total phosphorus (TP) as a result of shrub canopy and varying rates of rainfall. Activities of hydrolytic enzymes (β-1,4-glucosidase, β-1,4-N-acetylglucosaminidase, alkaline phosphatase and leucine aminopeptidase) were higher in under-canopy soil than in outside-canopy soil, among which C-acquisition enzyme β-1,4-glucosidase and P-acquisition enzyme alkaline phosphatase were also higher in soil of high rainfall. The overall pattern of enzyme activities did not show difference between under- and outside-canopy soils, but it separated the sites of high rate from that of low rates of rainfall. This pattern was primarily driven by variation in soil physiochemical properties rather than variation in soil microbial community, suggesting that distribution pattern of enzyme activities may be more sensitive to variation in rainfall than to shrub canopy. In conclusion, our study shows that shrub species A. gmelinii can shift soil microbial community to be fungal-dominant and increase hydrolytic enzyme activities, and such effect may depend on local climatic variation, e.g. rainfall changes in the semiarid land. The findings of this study highlight the important roles of shrub vegetation in soil biological functions and the sensitivity of such roles to climatic variation in semiarid ecosystems.